New data on bats hibernating in underground sites in Vilnius, Lithuania - Baranauskas, Kazimieras (2006)
Investigations into bat diversity and abundance were carried out in Vilnius 2005. Ten bat hibernation sites were investigated in the city where six bat species were found: Daubenton's bat (Myotis daubentonii), pond bat (Myotis dasycneme), Brandt's /whiskered bat (Myotis brandtii/mystacinus), brown long-eared bat (Plecotus auritus), barbastelle bat (Barbastella barbastellus) and northern bat (Eptesicus nilssonii). More than 820 bats roosted in Vilnius: Daubenton's bats constituted 62.5 %, barbastelle bats - 11.1% and pond bats - 10.7%. Pond bats, Daubenton's bats and barbastelle bats made up the largest known hibernating populations in south-eastern Lithuania. Brandt's/whiskered bats have been recorded in Vilnius hibernation sites for the first time.